Village Tourism Promotion Through Virtual Tour - I Dewa Gde Satrya (Ilomata International Journal of Management, 2023)
Introduction/Main Objectives: The COVID-19 pandemic has sparked creativity among tourism actors. Tourism villages as one of the tourist attractions, conduct virtual tours to introduce their attractions and facilities. The purpose of this study is to describe the role of virtual tours as a promotional medium in increasing interest in visiting village tourism. Background Problems: with the policy of limiting tourist travel, the tourism industry has experienced a decrease in the number of tourist visits. Digitalization is a way to maintain relationships with consumers and carry out promotions through virtual tours. The formulation of the research problem is what is the role of virtual tours as promotional media in increasing interest in visiting village tourism? Novelty: The novelty of this research lies in the use of virtual tours as a promotional medium to increase millennial tourist interest by involving relevant stakeholders. Research Methods: research was conducted with a qualitative approach. Primary data was obtained through focus group discussions and interviews during the virtual tour. Secondary data was obtained through relevant literature. Finding/Results: a virtual tour of the three tourist villages that became the case studies in this study, namely Nepal Van Java in Central Java and Sade Village in West Nusa Tenggara, succeeded in providing information that attracted millennial tourists to visit. Conclusion: the virtual tour is an effective promotional medium in increasing interest in visiting tourist villages.